1998
DOI: 10.4141/s97-006
|View full text |Cite
|
Sign up to set email alerts
|

In situ amelioration of sodic minespoil with chemical amendments and crop management. I. Soil chemical properties

Abstract: . 1998. In situ amelioration of sodic minespoil with chemical amendments and crop management. I. Soil chemical properties. Can. J. Soil Sci. 78: 359-365. Sodic minespoils, which often have undesirable properties that limit plant growth, may be ameliorated by chemical amendments. The objective of this study was to determine the effectiveness of sulfur and gypsum amendments in conjunction with crop management (summerfallow/barley rotation and continuous forage) in reducing the sodicity of a calcareous, sodic, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Third, many studies have reported that growing salt tolerant species could improve soil physical and chemical properties in saline soils 21–23. An increase in soil nutrients could also positively affect plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Third, many studies have reported that growing salt tolerant species could improve soil physical and chemical properties in saline soils 21–23. An increase in soil nutrients could also positively affect plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen cycling (Fyles 1984) became better understood. Amendments such as gypsum and sulfur were used to reduce sodicity (Sansom et al 1998a(Sansom et al , 1998b. Fly ash chemistry and minerology were studied by Warren (1983).…”
Section: Soil Reclamation Researchmentioning
confidence: 99%
“…This may be attributed to reduced evapotranspiration in the fallow/barley subplots. The soil moisture available to percolate in these subplots may have accelerated the leaching of salts, thus improving the ameliorative effects of the chemical amendments studied (Sansom et al 1998).…”
Section: Volumetric Moisture Contentmentioning
confidence: 99%
“…Fallow/barley subplots with higher TSW than forage subplots likely had increased salt leaching as indicated by the lower electrical conductivities in both amended minespoil layers (depth of 20-35 cm and 40-55 cm) under the fallow/barley versus the forage subplots in 1995 (Sansom et al 1998). …”
Section: Total Soil Watermentioning
confidence: 99%
See 1 more Smart Citation